The penny : a novel - Meyer, Joyce, 1943-; Bedford, Deborah (New York : FaithWords, 2007)
After taking a job at the local jewelry store, Jenny Blake becomes friends with the mysterious owner.
Keywords: Female friendship -- Fiction; Sexually abused teenagers -- Fiction; Saint Louis (Mo.) -- Fiction; Christian fiction; Large type books